The Tithe War in Ireland, 1830-1838 - Reid, David Patrick (Trinity College (Dublin, Ireland). Department of History, 2013)
The arguments and narrative contained in this thesis were mainly constructed from a detailed examination of four broad categories of primary sources. Firstly, it was necessary to research the mass of state paper material generated by the Dublin Castle administration in the years between 1830 and 1838. The state papers contain the most important manuscript material relating to the Tithe War, and their extent, variety, veracity and pertinence meant that their comprehensive reading, assessment and forensic examination forms the basis of the arguments contained in this thesis. Parliamentary Papers proved to be a second set of invaluable sources in providing information relative to, and perspectives on, the Tithe War.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin